Examining Facebook practice : the case of New Zealand provincial rugby : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Sport and Exercise at Massey University, Palmerston North, New Zealand - Cole, Jason (Massey University, 2016)
Social media have become a defining feature of 21st century communications. Conceived in 2004 Facebook has risen from relative obscurity to become the most visited website in the world. While social media use has grown exponentially, so too has its influence. Sport organisations were quick to capitalise on Facebook’s popularity particularly with the introduction of brand pages in 2010. The trend is no different particularly in New Zealand Rugby’s (NZR) National Provincial Championship (NPC). However recent research indicates a lack of understanding and consistency in evaluating effectiveness within the context of Facebook. Scholars have further acknowledged a need to move beyond simple metrics as measures of performance. Using a mixed method approach this case study of four NPC rugby teams investigated the understanding of effective Facebook practice. Thematic analysis of qualitative questionnaires completed by each page’s main administrator explored their understanding of effective Facebook practice. The researcher also utilised an auto-ethnographic journal to document his own experience of managing one of the participating brand pages. Page performance was also investigated through analysis of Facebook insights data to establish how it may be more accurately interpreted to inform best practice. Results reveal that administrators perceive lack of control, maintaining credibility, guaranteeing reach and resource allocation to be the most prominent challenges faced by these brand pages. Such issues provide further tensions when attempting to justify social media use and effectiveness within sport organisations. Furthermore, teams are faced with commercial obligations to post sponsor content that may negatively impact user engagement. In addition, findings suggest that contrary to popular belief, greater total network sizes do not guarantee greater reach and engagement. It is proposed that teams consider proportional measures of performance when seeking to measure Facebook performance. Holistically the research sets a platform that can be used in future studies to tangibly connect Facebook effectiveness to organisational strategy and objectives.
Keywords: Facebook (Electronic resource); Rugby Union football; Public relations; Marketing; Social media; New Zealand; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Sports